Enabling Asia to Stabilise the Climate - Nishioka, Shuzo (Springer Nature Singapore : Imprint: Springer, 2016)
This book presents good practices in Asia and ASEAN countries for effectively promoting advances in response to climate change, which can help to achieve sustainable development in Asia and around the world. As a proposal, the aim is to influence the discussions at COP 21 by providing a positive agenda with concrete actions from an Asian perspective. The book is divided into three parts. Part 1 describes the greenhouse gas (GHG) reduction scenario from an Asian perspective and in line with global 2 ° targets. Based on modeling analysis, the studies demonstrate the theoretical potentials and send the policymakers at COP 21 the positive message that "Asia can reach the target." As Asian countries vary in terms of their economic strength, country-specific scenario studies for the two giants China and India as well as for Japan and Vietnam are introduced to show the different approaches for each country. Part 2 shows successful examples of how modeling analysis are reflected in actual policy development, which provides practical guidelines to help policymakers develop their own roadmaps with stakeholder dialogue, not only in Asia but also in other regions of the world. The Nationally Appropriate Mitigation Action (NAMA) roadmap development in Thailand as well as the Iskandar Malaysia project show at the country and city level how researchers and policymakers are working closely to succeed. Part 3 focuses on a number of sector-specific activities including transportation, forestry, capacity development, and inventory work in Asia. Rather than discussing the Low Carbon Society (LCS) concept in detail, the respective chapters highlight unique, concrete, and practically applicable examples from Asia, showing how Asian countries are addressing climate change mitigation issues in a collaborative manner, an approach that can be replicated in other regions. While the ultimate goal of this book is to facilitate international climate regime making, local government and international organizations (United Nations, World Bank, and others) officers, researchers, international NGO/NPOs, consultants, students (particularly those studying international relationships or environmental studies), as well as reporters will find this book useful in broadening their understanding of low-carbon development in Asia.